2005
DOI: 10.2527/2005.83102380x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth performance and zinc absorption, retention, and excretion in weanling pigs fed diets supplemented with zinc-polysaccharide or zinc oxide1

Abstract: Fifty weanling crossbred pigs averaging 6.2 kg of initial BW and 21 d of age were used in a 5-wk experiment to evaluate lower dietary concentrations of an organic source of Zn as a Zn-polysaccharide (Zn-PS) compared with 2,000 ppm of inorganic Zn as ZnO, with growth performance, plasma concentrations of Zn and Cu, and Zn and Cu balance as the criteria. The pigs were fed individually in metabolism crates, and Zn and Cu balance were measured on individual pigs (10 replications per treatment) from d 22 to 26. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 26 publications
1
40
1
3
Order By: Relevance
“…However, in other studies, pharmacological Zn from ZnO had no effect on plasma Cu concentration (Buff et al, 2005;Shelton et al, 2011) or actually increased plasma Cu concentration, except when both Zn and Cu were combined in the diet (Shelton et al, 2011). Differences in the results between the present trial and the previously reported trials may be associated with the level of Cu or Zn fed or the source of Cu supplied in the diets.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…However, in other studies, pharmacological Zn from ZnO had no effect on plasma Cu concentration (Buff et al, 2005;Shelton et al, 2011) or actually increased plasma Cu concentration, except when both Zn and Cu were combined in the diet (Shelton et al, 2011). Differences in the results between the present trial and the previously reported trials may be associated with the level of Cu or Zn fed or the source of Cu supplied in the diets.…”
Section: Discussioncontrasting
confidence: 79%
“…This is in contrast with the apparent faecal Zn digestibility of the present trial, which was negative and increased as ZnO supplementation increased to 3500 mg/kg. However, Buff et al (2005) reported a 53% increase in Zn absorption and a 60% increase in Zn retention when pigs were fed 2000 mg/kg Zn from ZnO compared with a basal diet containing 162 mg/kg Zn. The discrepancies in the data may be due to collection methods, the time and age of the pigs at sampling, ADFIand thus average daily Zn intake -and the bioavailability of the source of Zn used.…”
mentioning
confidence: 97%
“…Ward et al [17] also reported that 250 mg/kg of Zn as Zn-methionine increased growth performance of weanling pigs equal to that of 2,000 mg/kg of Zn as ZnO. Moreover, supplementation of weanling pig diets with 300 or 450 mg/kg of Zn as Zn-PS maintained phase 2 (d 14 to 35) and overall growth performance similar to that obtained with 2,000 mg/kg of Zn as ZnO [18]. Our previous study showed supplementation with appropriate zinc glycine chelate (Zn-Gly) can improve the growth performance and immunological capacity of broilers [16].…”
Section: Introductionmentioning
confidence: 69%
“…It was demonstrated that feeding weaning pigs a diet containing 250 mg/kg Zn as ZnMet increased growth performance in a similar way to pigs fed a diet containing 2000 mg/kg Zn as ZnO (Ward et al, 1996). Moreover, it was shown that growth performance of pigs fed a diet containing 300 or 500 mg/kg Zn as Zn-Polysaccharide (Zn-PS) did not differ from that of pigs fed 2000 mg/kg Zn as ZnO; however, feeding 300 mg/kg Zn as Zn-PS decreased Zn excretion by 76% compared with feeding 2000 mg/kg Zn as ZnO (Buff et al, 2005). In addition, the adverse effect of high Zn intake on copper availability has to be considered (Maret and Sandstead, 2006).…”
Section: Discussionmentioning
confidence: 99%